Kebijakan Pemerintah Islam Klasik Terhadap Masyarakat Miskin - Saiful Bahri (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2013)
This study will describe the Islamic classical government wisdom about poverty. The result pointed out explains that the Prophet Muhammad, his friends (Khulafa’ ar-Rasyidin) and Umayya empire never let poverty right.